Миропостижение как стратегия философии образования - Мищенко, Виктор Иванович (Національна академія Національної гвардії України, 2017)
Проанализировано соотношение педагогики, психологии и философии образования, на основе синергетической парадигмы выделены три иерархических уровня их взаимодействия. В этой синергетической системе специфика философии образования рассматривается авторов в рефлексии, концентрации усилий на смысловых аспектах педагогической деятельности. Актуальным представляется анализ кризисных явлений и процессов в образовании. Продуктивным видится использование постпозитивистской методологии в анализе социальных и культурных процессов в обществе, науке, искусстве, влияющих на процесс образования, расширения диапазона предмета исследования, как на мегауровне, так и в исследовании экзистенциальных основ бытия личности. В предметном логическом поле современного образования рассматривается проблема формирования духовного облика, определены три взаимосвязанных компонента духовного облика личности: открытость миру, интеллигентность и пассионарность. Выявлено системообразующее свойство духовного облика личности – чувств святости, для формирования которого автор предлагает осуществлять обучение на основе катарсического мировосприятия, разработать и реализовать новую философскую стратегию современного образования на основе интеграции знаний о современном мироустройстве – миропостижение. Миропостижение есть соединение философской теории с новейшими научными исследованиями, единство когнитивных и ценностных параметров знания процесс духовного освоения человеком Вселенной, стратегия развития современного образования.

The correlation of pedagogy, psychology and philosophy of education is analyzed, on the basis of the synergetic paradigm three hierarchical levels of their interaction are distinguished. In this synergetic system, the specificity of the philosophy of education is considered by the author in reflection, the concentration of efforts on the semantic aspects of pedagogical activity. An actual analysis of crisis phenomena and processes in education is presented. The use of postpositivist methodology in the analysis of social and cultural processes in society, science and art, affecting the process of education, expanding the range of the subject of research, both at the mega-level, and in the study of the existential foundations of the being of a person is seen as productive. In the subject logical field of modern education, the problem of the formation of the spiritual appearance is considered, three interconnected components of the spiritual personality are identified: openness to the world, intelligence and passionarity. The system-forming property of the spiritual image of the person - feelings of holiness is revealed, for the formation of which the author proposes to teach on the basis of a cathartic world view, to develop and implement a new philosophical strategy of modern education based on the integration of knowledge about the modern world order - world-perception. World- perception., there is a combination of philosophical theory with the latest scientific research, the unity of cognitive and value parameters of knowledge, the process of spiritual mastering by the man of the universe, the strategy of development of modern education.
World outreach as a strategy of the philosophy of education
Keywords: философия образования; педагогика; катарсическое мировосприятие; духовный облик; открытость миру; интеллигентность; пассионарность; духовность; philosophy of education; pedagogy; catharsic world view; spiritual image; openness to the world; intelligence; passionarity; spirituality; world-perception